Os processos de comunicação e mediação da informação em uma indústria de alta produtividade do setor sucroalcooleiro no estado de São Paulo - Silva, Marcio Ferreira da [UNESP] (2013)
The sugar-alcohol sector in Brazil has been the subject of incisive discussions about its potentiality as a world energy alternative. The recent expansion of foreign companies in acquisitions and mergers seems to answer this question. At the same time these industries need to expand their investments in research and innovation. Observing the importance that the information carries out on this kind of organization, the problem of this research is how one deals with the mediation and communication processes of the internal information in an industry of high productivity in the sugar-alcohol sector of São Paulo state. Therefore, it was aimed to analyze about the mediation and communication processes of the internal information in an industry of high productivity in the alcohol of São Paulo state. As to its methods, the research is about a case-study, using a non-probability sampling. The techniques of data collection selected were: the interview, the questionnaire and the diary. The approach of the essay involved three main lines of reasoning, the action of the mediator agents of information in these spaces, the internal communication process in the industry and the information and communication technologies integrated to the communication process. In relation to the professionals in the internal area, it is clear the identification of necessary attributes to the mediator agents identified in the daily activities of the industry and included in different departments. In the field of communication recognized its strategic importance and presented important points that reveal the use of the communication of information in this kind of environment, mainly by informal means. After the data and analyses collection the most used means in the communication and mediation information are presented. The technologies involved have been... (Complete abstract click electronic access below)